Pengaruh Kompetensi Sosial Guru terhadap Sikap Sosial Siswa di Madrasah Tsanawiyah Salafiyah Syafiiyah Seblak Diwek Jombang - Siti Fa’iz Fauziah; Suwandi Suwandi (Institut Agama Islam Negeri Kediri, 2021)
Abstract: This research is intended to describe and explain the impact of teacher's social skills on the students' social attitudes at tsanawiyah salafiyah syafiiyah cure. Regarding this, we will discuss the level of social competence of students and teachers of tsanawiyah salaf ha ha ha ha shafi 'iyah immediately debunched, and student social attitudes. General tsanawiyah salafiyah saii 'iya ya ya ya cure, and that is.They contribute to the teacher's social skills. Leverage. Disciple Social madrasah tsanawiya saiafiya 'ii 'iya ya cure cure. The study is a field study using a quantitative approach. The data-collection technique used was either a questionnaire or an angket. Based on research already done, the teacher's social competence at tsanawiyah salafiyah fi I 'iyah Once quacked on jombang is in a good category as many as 16 teachers with 50 percent value of propercentage. As for the student social attitude at the madrasah tsanawiyah Saiaf yah shafi 'iyah healer is listed in good categories 15 students with a value of 47 percent. Further after a data analysis, researchers have concluded that there is an influence of teacher social competence toward the student's social attitudes at tsanawiyah salafiyah interi 'ii 'iya ya ya failed. This can be deduced based on calculations already made with x and y's value corelations on the p-valu value chart in the sig column (2-tailed) 0,000 less than 0.05 levels of accuracy which means ha received and ho rejected. Abstrak: Penelitian ini dilakukan untuk mengetahui pengaruh kompetensi sosial guru terhadap sikap sosial siswa di Madrasah Tsanawiyah SaIafiyah Syafi’iyah Seblak Diwek Jombang. Pendekatan peneIitian yang dipakai oIeh peneIiti iaIah pendekatan kuantitatif dengan cara menyebarkan angket atau kuesioner. Dari penelitian ini dapat ditarik kesimpulan bahwa kompetensi sosial guru di Madrasah Tsanawiyah Salafiyah Syafi’iyah Seblak Diwek Jombang sudah baik. Hal ini didasarkan pada hasil angket yang teIah dilakukanoleh peneliti, dengan hasil jawaban angket dari responden mengenai kompetensi sosial guru dimana kategori baik sebanyak 16 guru dengan nilai prosentase 50 persen dan kategori sangat baik sebanyak 6 guru dengan nilai prosentase 19 persen. Sikap sosial siswa di Madrasah Tsanawiyah SaIafiyah Syafi’iyah SebIak Diwek Jombang juga sudah sangat baik. Hal ini berdasarkan hasil angket dimana kategori baik sebanyak 15 siswa dengan nilai prosentase 47 persen dan kategori sangat baik sebanyak 9 siswa dengan nilai prosentase 28 persen. Disini kita dapat menyimpulkan bahwa terdapat pengaruh kompetensi social guru terhadap sikap sosial siswa di Madrasah Tsanawiyah Salafiyah Syafi’iyah Seblak Diwek Jombang. Hal ini disimpulkan berdasarkan perhitungan yang telah dilakukan melalui uji korelasi hasil X dan Y pada tabel coreIations niIai p-value pada koIom sig(2-taiIed) 0,000 kurang dari 0,05 level of significant yang berarti Ha diterima dan H0 nya ditoIak.